Economic shocks and changes in school attendence levels and education expenditure in Peru - Escobal, J; Saavedra, J; Suárez, P (2005)
Despite improvements in enrolment rates in recent decades, the Peruvian school system still has serious shortcomings. A high drop-out rate in secondary school stems from the fact that the system does not provide adequate support for students who fall behind, cannot afford to go to school, or would rather work than continue their education. The situation becomes particularly difficult for households who face economic shocks that force them to reassign time and money away from education. This paper studies the effect of economic shocks on household investment patterns in Peru using a sample of 6- to 14-year-old children going through the Peruvian education system. Most studies that have tried to determine the effect of economic shocks on human capital (investment in education, skills training, health, and well-being) have focused on an analysis of changes in school enrolment. The authors here suggest a more comprehensive analysis of the possible mechanisms through which investment in education can be affected. The conclusions presented here support the hypothesis that shocks have an impact on the quality, rather than the length, of education. The evidence shows that shocks do not necessarily effect the school drop-out rate or the rate of ‘over-age schooling’ (of children at least one year older than the age expected for their grade). The evidence does demonstrate, however, that negative shocks do reduce the effective accumulation of human capital through cuts in spending on education, in both urban and rural areas. Results are significant both when a short-term shock is brought about by changes in household income or expenses and when it is brought about by changes in employment status.